A praça da República de Niterói - Brito, Clélia Fernandes (1990)
This research clarifies the discussed history of the "Praça da República de Niterói" (Republic Square of Niterói), and rescues its artistic and cultural value as an ecletic architetonic complex of the beginning of the century. It also proves that the architects Emilio Dupuy Tessain (French) and Pedro Campofiorito (Italian) were its designers, and records the success of the campaign for the reconstruction of the square which was destroyed in 1971 and reinaugurated on December 5th, 1989. Thus it reassumed its role as a witness of a historical period of the city characterized by political disputes and urbanistic and administrative reforms.